Communications Under Siege: Colonial Legacy and Authoritarian Surveillance in India - Arun, P. (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
Under the guise of decolonizing and modernizing laws, the Bharatiya Janata Party-led National Democratic Alliance government has sought amendments in laws governing every aspect of digital communication in India, such as cellular mobile, instant messaging, news, and entertainment. The government has dramatically expanded its power to control and regulate different forms of digital communications, exerting significant influence over what people watch, read, hear, and think. This extensive authority enables the government to monitor, surveil, censor, and shape public mood and opinion, thus placing communications under siege. In today’s world, communication technologies are deeply embedded in our daily lives as we transmit, share, and broadcast information. In India, the enduring legacy of colonial surveillance powers continues to shape and influence the surveillance over digital communications. This Dialogue paper argues that authoritarian surveillance in India is not merely a direct manifestation of the colonial legacy of British rule, but rather a fusion of enduring authoritarian features rooted in the colonial past, and the prevailing authoritarian intentions and practices of the post-colonial present.